Relações de equivalência entre elementos de funções do primeiro grau para alunos do ensino fundamental - Seabra, Diego Felipe Silveira (Universidade Federal de São Carlos, 2014)
This master‟s thesis consists of a study, reported a paper format, about crucial variables present in the establishment of relations between elements of first degree functions. This study was conducted from the theoretical framework of Behavior Analysis and fits in a growing body of research on mathematical behavior. The teaching and learning of mathematics have been characterized as a difficult process, with unsuccessful results that generates a number of by-products, such as anxiety and aversion to mathematics, worsening a quite problematic panorama. In this context, this master‟s thesis reports a research which sought to analyze the effectiveness of the application of Behavior Analysis technology, specifically derived from the stimulus equivalence paradigm, for the establishment of relations between elements of first degree functions. The participants were submitted to a Matching to Sample procedure, though which relations AB and BC were trained, where A, B and C represent sets of elements related to first degree functions (graph, table, speech, etc). After training, tests of symmetry, transitivity and equivalence (BA, CB, BC, CA) were conducted in order to assess potential formation of equivalent stimuli classes, as well as generalization tests. The results showed that all participants formed equivalence classes and obtained 100% of correct responses in the generalization tests. This research sustains the possibility of effective application of stimulus equivalence paradigm to the establishment of complex mathematical repertoires.
Equivalence relations among elements of first-degree functions in elementary education students
Keywords: Psicologia; Equivalência de estímulos; Matemática - estudo e ensino; Comportamento matemático; Função do primeiro grau; Ensino fundamental; Stimulus equivalence; Mathematics learning; Math behavior; First degree functions; Elementary education; CIENCIAS HUMANAS::PSICOLOGIA